Hypophosphatasia: A Case of Two Patients With Spinal Cord Compression From Increase in Ligamentous Ossifications During Treatment. (5th March 2021) - Laroche, Michel; Couture, Guillaume; Faruch, Marie; Ruyssen‐Witrand, Adeline; Porquet‐Bordes, Valérie; Salles, Jean Pierre; Degboe, Yannick
ABSTRACT: Treatment with asfotase alfa has transformed the prognosis of hypophosphatasia in children and improves the bone and muscle signs in adults. The doses used in adults are the same as in children, whereas bone remodeling is different between them. We report on the cases of two patients treated with 1 mg/kg/day of asfotase alfa who developed spinal cord compression from spinal ossifications during treatment. The first patient, 50 years old, presented after 2 years of treatment with quadraparesis secondary to an increase in ossifications of the cervical vertebral ligaments. The neurological damage was resolved after laminectomy, and the patient was then treated for 18 months with doses of 80 mg per week, without recurrence of the bone and muscle signs. The second patient, 26 years old, 78 kg, developed pain and cervical stiffness with pyramidal tract irritation secondary to ossifications of the vertebral ligaments. This improved with a reduction of doses to 80 mg/week, which then, after 6 months of follow‐up, enabled maintained improvement of the bone and muscle pain that was initially obtained. To our knowledge, these are the first reported cases of increased spinal ligamentous ossifications with neurological complications. Biological monitoring in adults does not seem to enable asfotase alfa doses to be adjusted. The levels of serum alkaline phosphatase (ALP) while on the recommended treatment of 1 mg/kg/day are significantly supraphysiological (5000 to 20, 000 IU) and the assays of pyrophosphate and pyridoxal phosphate are not correlated with clinical efficacy. In both of our patients, the treatment with 80 mg of asfotase alfa per week, which was proposed after the occurrence of spinal complications, seemed as effective, after a follow‐up of 18 months and 6 months, as the initial treatment for improving the bone and muscle signs, and could be provided as "attack" doses after healing of the pseudoarthroses. © 2021 American Society for Bone and Mineral Research © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.